Reporting Consolidated Gains and Losses on Subsidiary Stock Issuance. - Davis, Michael L.; Largay III, James A. (The Accounting Review, 1988)
Abstract For years the SEC had required companies that experienced increases in their equity in subsidiaries due to a subsidiary stock issuance to enter that increase (or ‘gain’) in Paid-in Capital. In 1983, the SEC changed its views on this issue in Staff Accounting Bulletin No. 51 [SEC, 1983]. Following the conclusions of an AICPA Issues Paper on the subject, the Commission decided to offer companies the option of reporting such gains from subsidiary stock issuances either in capital or in income in consolidated financial statements. This treatment was later extended to stock issuances of nonconsolidated equity investees, and companies began reporting these gains in income. This paper critically examines the view taken in the Issues Paper and reflected in SAB 51, that gains on subsidiary stock issuances are similar in substance to gains realized when the parent sells part of its investment in the subsidiary It also reports on the treatment of these transactions in practice—and the window—dressing potential-by companies reporting them. We conclude that while a subsidiary stock issuance is similar in many respects to a parent's sale of its subsidiary's stock, there are important differences. Moreover, the proper accounting may depend on the theory of consolidation adopted. Public reporting of these transactions is often inadequate, particularly with respect to tax effects (an unsettled area in which standard-setting may be needed) and footnote disclosure.